Salt Stress Reduced the Seedling Growth of Two Larch Species Under Elevated Ozone - Sugai, Tetsuto; Yannan, Wang; Watanabe, Toshihiro; Satoh, Fuyuki; Qu, Laiye; Koike, Takayoshi (Frontiers in Forests and Global Change, 2019)
The effect of elevated ozone (O3) and soil salinization with alkaline salts in northeastern (NE) China is a serious concern in the success of the national replanting project. As the areas planted exceed 4 million hectares in China, we must consider the future afforestation after thinning and harvest at some parts of them. Here, we investigated the effects of O3 and salt stress on seedlings of Dahurian larch (Larix gmelinii var. japonica; DL) and Japanese larch (L. kaempferi; JL). The two species of seedlings were exposed to elevated O3 [approximately 70 nmol mol-1] and ambient control [approximately 40 nmol mol-1] for one growing season in an open top chamber (OTC) system that simulated the salinity in NE China [alkaline salt, NaHCO3 : NaCl = 9:1, 20mM Na+]. The seedlings under salt free treatment received tap water. Effects of O3 on the growth of both larches were not significant, although the LMA of JL was reduced more than that of DL seedlings. Further, the combined effects of O3 and salt stress were not significant. This may be attributable to the stronger effects of salt stresses on both larch seedlings. Salt stress decreased the total dry mass in both larch species by more than 10%. DL seedlings showed specific salt tolerance in absorption of some mineral nutrients. Although salt stress reduced Ca and Mg content in needles, we found the degree of reduction was lower in DL than JL, with specific salt tolerance of mineral homeostasis in DL seedlings. Our results indicated that DL seedlings may be future candidate afforestation species even in saline soil and O3 levels less than 70 nmol mol-1.